Adolescent Popularity: Distinct Profiles and Associations with Excessive Internet Usage and Interpersonal Sensitivity. - Stavropoulos, Vasileios; Barber, Emily; de Sena Collier, Gabriel; Snodgrass, Jeffrey G.; Gomez, Rapson (Child Psychiatry & Human Development, 2022)
Peer popularity constitutes a pivotal developmental task to adolescents' current and future adaptation. This study identified distinct adolescent popularity profiles and explored their links with excessive Internet usage and interpersonal sensitivity. The sample included 2090 students attending Greek high schools (M = 16.16, SD = 0.91). Their popularity was measured via self-report and peer sociometric means. They also responded to the Internet Addiction Test (IAT) and the Interpersonal Sensitivity subscale of the Symptom Checklist-90-Revised (SCL-90-R). A sequence of latent profile analysis, ANOVAs and linear regression models were performed. Three distinct popularity profiles were revealed: the "Average Confident" (68.4%), the "Socially Vulnerable" (26.8%), and the "Insecure Bi-Strategic" (4.8%). These profiles did not significantly vary regarding their Internet usage and interpersonal sensitivity behaviours. Interestingly, lower self-perceived popularity predicted higher interpersonal sensitivity, whereas higher actual popularity predicted excessive Internet use. Findings have important implications for student-tailored mental health prevention and intervention practices.